‘Greek colonisation’ and Mediterranean networks: patterns of mobility and interaction at Pithekoussai - Donnellan, Lieve (Journal of Greek Archaeology, 2016)
Pithekoussai, present-day Ischia, a small island in the Bay of Naples had completely escaped the attention of Antiquarians and government functionaries—some more, some less diligently excavating the many rich archaeological sites around Naples and the Vesuvius since the 17th century—until native resident and archaeologist Giorgio Buchner uncovered the first tombs, shortly after WW II, and with it, opened a previously neglected chapter in Greek history, that of ‘Euboean colonisation’. Since the discovery of Pithekoussai, scholarly attention for Greek, especially Euboean ‘colonisation’ has skyrocketed, and the Euboeans have been hailed as the first Greek prospectors, pioneers, the openers of the Mediterranean after the Dark Ages and the creators of the pivotal Greek institution of oversees colonisation—an institution which would transform the Greek world thoroughly. The increased attention for the Euboean colonisation movement helped define Greek colonial studies as a separate subject of study, after pioneering work by scholars such as that of Jean Bérard and Tom Dunbabin, who collected literary evidence and confronted it with the, at that time, scarcely known archaeological remains. Pithekoussai, however, has uninterruptedly been at the heart of studies and debates on ancient Greek ‘colonisation’.